Demonstration Method with TPACK Approach to Improve the Writing Ability of Procedure Text in Fourth Grade - Mulyanah, Rizka; Maulana, Farid Rizqi; Wardana, Deni (Yayasan Pendidikan Bima Berilmu, 2024)
The observation results reveal that the teacher did not integrate technology into all learning processes, resulting in poor writing skills among students. The researcher aimed to evaluate the efficacy of the TPACK-based demonstration approach in enhancing procedural text writing proficiency. A quasi experimental pre-test post-test control group design was employed to examine this effect. The target population for this study included all fourth grade students at SDN Kedaung Wetan 2. A sample of 40 students was selected, with 20 students from class 4A assigned to the control gorup and 20 students from class 4B assigned to the experimental group. The instrument used in this study was a written test. Data analysis was performed using the SPSS 27 program. Both the Paired Sample T-Test (Sig. (2-tailed) = 0.001) and the Independent Samples T-Test (Sig. (2-tailed) = 0.075) yielded statistically significant results (p = 0.05), indicating that the null hypothesis (Ho) can be rejected in favor of the alternative hypothesis (Ha). This suggests a significant difference between the learning outcomes of students receiving traditional instruction. Furthermore, the N-Gain Score analysis revealed an average improvement of 56% in the learning outcomes. This finding supports the notion that the TPACK integrated method has a positive influence on students ability to write procedure texts.